2015
DOI: 10.4049/jimmunol.1303188
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol Promotes M1-like Macrophage Activation through Cadherin-11 To Aggravate Temporomandibular Joint Inflammation in Rats

Abstract: Macrophages play a major role in joint inflammation. Estrogen is involved in rheumatoid arthritis and temporomandibular disorders. However, the underlying mechanism is still unclear. This study was done to verify and test how estrogen affects M1/M2-like macrophage polarization and then contributes to joint inflammation. Female rats were ovariectomized and treated with increasing doses of 17β-estradiol for 10 d and then intra-articularly injected with CFA to induce temporomandibular joint (TMJ) inflammation. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 40 publications
2
36
0
2
Order By: Relevance
“…Female rats have higher levels of plasma estrogen than male rats, and previous studies showed that estrogen aggravates TMJ inflammation and TMJOA (Kou et al., , ; Wang, Kou, He et al., ). We hypothesized that estrogen might contribute to the enhanced sensitivity of female FLSs to response to inflammatory stimulus.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Female rats have higher levels of plasma estrogen than male rats, and previous studies showed that estrogen aggravates TMJ inflammation and TMJOA (Kou et al., , ; Wang, Kou, He et al., ). We hypothesized that estrogen might contribute to the enhanced sensitivity of female FLSs to response to inflammatory stimulus.…”
Section: Resultsmentioning
confidence: 96%
“…TMJOA is approximately twice as prevalent (and more severe) in women than in men (Carlsson, ; Israel et al., ; Stegenga et al., ; Zhao, & Ma, ). It is not surprising that previous studies have tried to explain the sex difference in TMJOA prevalence by focusing on sex hormones, such as estrogen, which has been considered to play an important role in the symptomatology of female‐predominant TMDs, synovitis, chondrocyte apoptosis, and inflammatory pain (Flake, Hermanstyne, & Gold, ; Guan, Kerins, Bellinger, & Kramer, ; Kou et al., , , ; Wang et al., ; Wu et al., ). The TMJ synovial membrane consists of a condensed one‐ to three‐cell‐thick lining layer of synoviocytes that overlies the loose connective tissue of the synovial sublining (Nozawa‐Inoue et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Cell culture NR8383 rat alveolar macrophages were purchased from American Type Culture Collection (ATCC ® CRL2192 ™ ; Manassas; USA). Cells were cultured in Dulbecco's Modified Eagle Medium DMEM, high glucose [27,28] (Sigma-Aldrish; St. Louis; USA), supplemented with 15% Fetal Bovine Serum, FBS (Sigma-Aldrish; St. Louis; USA), 100 U/mL penicillin and 100 g/mL streptomycin, 4 mM l-glutamine and 0.25 μg/mL of amphotericin B (Sigma-Aldrish; St. Louis; USA). Cells were cultured at 37 °C in humidified chamber with 5% CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…During the later phase of disease, alternatively activated macrophages (M2) release anti-inflammatory cytokines and promote tissue repair (Gordon, 2003, Jiang et al, 2014, Mikita et al, 2011, Miron et al, 2013, Miron and Franklin, 2014). However, estrogen effects on the M1:M2 ratio is controversial; while some reported that estrogen induces M1 phenotype in macrophages; others have shown that estrogen treatment promotes M2 phenotype in microglia (Drew et al, 2003, Habib and Beyer, 2015, Kou et al, 2015, Toniolo et al, 2015). Furthermore, the effect of estrogen treatment on microglia during EAE has not been demonstrated.…”
Section: Introductionmentioning
confidence: 99%